Effect of pressures on macro-/microstructures and mechanical properties of A380 aluminum alloy - YU Bai-shui; XING Shu-ming; AO Xiao-hui; SUN Chao (工程科学学报)
This study investigated the microstructures and the mechanical properties of the A380 alloy solidified at different squeeze pressures by polarizing microscopy, scanning electron microscopy, image analysis, and tensile test. The obtained results show that the microstructures of the squeeze casting specimens are much finer than those of gravity casting specimens. Moreover, the porosity and the mechanical properties of the squeeze casting specimens are remarkably improved compared with those of the gravity casting specimens. The size of the dendrite arm and the porosity decrease when the squeeze pressure is increased from 0 MPa to 75 MPa in the squeeze casting process. The eutectic volume fraction of the specimen increases, while the secondary dendrite spacing decreases. The size of the needle-like β-Al5 FeSi phase significantly decreases. In addition, a few α-Al8 (Fe,Mn)3Si2 phases with Chinese characters are observed in the grain boundary. The influence of the pressure on the microstructures, second-phase morphology, and mechanical properties of the squeeze casting specimens does not significantly improve with the increasing squeeze pressure when the squeeze pressure is larger than 75 MPa. The tensile strength and the elongation of the A380 alloy when the squeeze pressure is 75 MPa increase by 19% and 65%, respectively, compared with those of the gravity casting specimens.